The Effect of Electronic Word of Mouth, Destination Image on Tourist Visiting Decisions at Nagari Tuo Pariangan Tourism Object - Hardiana Widyastuti; Yomi Satifa Putri (Universitas Airlangga, 2023)
Background: Tourism at this time has become one of the critical needs for most people, this can be seen from the increased interest in tourism which is side by side with digital promotion through EWOM in the tourism sector which is rampant on social media. With the high intensity of internet use, especially on social media platforms, making digital promotions through social media provides excellent tourism marketing opportunities. Objective: This study aims to analyze the effect of electronic word of mouth and destination image on the decision to visit tourists at the Nagari Tuo Pariangan tourist attraction. Method: The data used in this study were obtained from primary data and secondary data. The data analysis method used is descriptive analysis and SEM-PLS analysis with a sample of 130 respondents, using a non-probability sampling method. Results: The results of this study indicate that electronic word of mouth has a positive and significant effect on destination image, destination image has a positive and significant effect on visiting decisions, and electronic word of mouth has a positive but not significant effect on visiting decisions. However, there are mediating variables that can influence. Conclusion: The results of the SEM-PLS analysis also show a positive and significant effect between the electronic word-of-mouth variables on the destination image and decision visit. Keywords: destination image; electronic word of mouth; the decision to visit; SEM-PLS